27.3k views
1 vote
-4(3 - 2x) + 2x = 2x - 8

2 Answers

3 votes

Answer:

x = 1/2 = 0.5

Explanation:

Subtract 2x from both sides:

-4(3-2x) + 2x - 2x = 2x - 8 - 2x

Simplify:

-4(3 - 2x) = -8

Divide both sides by -4:

-4(3-2x) / -4 = -8/-4

Simplify:

3 - 2x =2

Subtract 3 from both sides:

3 - 2x - 3 = 2 - 3

Simplify:

-2x = -1

Divide both sides by -2:

-2x/-2 = -1/-2

Simplify:

x = 1/2

User Dwynne
by
5.3k points
1 vote

Answer:

x =
(1)/(2)

Explanation:

Given

- 4(3 - 2x) + 2x = 2x - 8 ← distribute and simplify left side

- 12 + 8x + 2x = 2x - 8

10x - 12 = 2x - 8 ( subtract 2x from both sides )

8x - 12 = - 8 ( add 12 to both sides )

8x = 4 ( divide both sides by 8 )

x =
(4)/(8) =
(1)/(2)

User Cylon Cat
by
5.6k points